How e-learning systems may benefit from ontologies and recommendation methods to efficiently personalise resources. (26th January 2010) - Kerkiri, Tania; Manitsaris, Athanassios; Mavridis, Ioannis
Knowledge management systems suffer from the efficient management of the information they maintain. Current e-learning systems, is an application of a progressively more complex information domain, as they increasingly enhance their courses with the variety of web based resources to meet the educational needs of their participants. Thus, they face the problem of managing and personalising this knowledge. To confront this problem they already benefited from the semantic web technologies. Ontologies, a cardinal asset towards augmenting the interoperability among web applications, anticipate the accuracy of the retrieved data by means of effective matching of the user requirements. In this paper ontologies are explored to personalising resources. The framework of an e-learning system is described and a methodology is proposed applying recommendation algorithms. Personalisation is achieved via handling related metadata of the attendants' personality and preferences, as well as, reputation metadata, thus anticipating their satisfaction and educational progress.